Needs Analysis of Augmented Reality Development on Microbiology Practical Guide of Virus Material - Rukiah Lubis; Meti Herlina (STAI Hubbulwathan Duri, 2022)
This study aims to describe the needs analysis of the development of an AR-based microbiology practicum guide on viral material. This type of research is the research and development (RD). The development model used in this research is to modify the 4D development model. The population in the study were students of the fifth semester of Biology Education, FKIP UMB and course lecturers. The instrument used is a needs analysis questionnaire for students and for course lecturers. The data were analyzed using descriptive analysis and the percentage of the number of answers given was divided by the total number of respondents multiplied by 100%. Based on the results of the study, it can be concluded that all students agree to develop an AR (microbiology practicum guideAugmented Reality)on virus material because it is important to use an AR-based practicum guide. In addition, based on the results of the analysis of the needs of the lecturers, the lecturers do not know or know the AR application. In addition, there is no specific microbiology practicum guide for AR-based virus material in the study program environment. The use of AR media-based practicum guides is one solution in understanding the content of the material, especially virus material. The thing that must be considered in the practicum guide is that the content and format must be complete and systematic so as to make it easier for students to understand the course of the practicum which contains materials, tools/materials, working methods to the format and reporting of results.